Implications of Labeling the Criminal Armed Group in Papua as a Terrorist Organization - Milda Istiqomah; Heru Kurniawan; Raras Natasya Anindita (Faculty of Law, Universitas Sebelas Maret, 2025)
Conflict and bloodshed continue in Papua, whether by governmental actors or the Criminal Armed Group. The Coordinating Ministry for Politics, Law, and Security declared the KKB in Papua a terrorist organisation in 2021 after classifying it as a separatist organisation. This study aims to look into what it means that the Papuan government called the KKB a